Coagulopathy of sepsis - Dempfle, Carl-Erik (Thrombosis and Haemostasis, 2004)
Disseminated intravascular coagulation (DIC) is a common phenomenon in patients with sepsis, but the clinical implications of this condition are not clear. Clinical trials with coagulation inhibitors have failed to show a significant benefit concerning survival. DIC is primarily a laboratory diagnosis, based on the combination of elevated fibrin-related markers (FRM), with decreased procoagulant factors and platelets. Non-overt DIC is observed in most patients with sepsis, whereas overt DIC is less frequent. Patients with overt DIC may display consumption coagulopathy and purpura fulminans. Consumption coagulopathy is a bleeding disorder caused by low levels of platelets and procoagulant factors associated with massive coagulation activation. Purpura fulminans is caused by widespread microvascular thrombosis, resulting in tissue necrosis. Treatment with drotrecogin alfa (activated) improves survival and other outcome parameters in severe sepsis, including a subgroup of patients fulfilling the laboratory criteria of overt DIC. No randomized trials demonstrating effective therapies in consumption coagulopathy have been published. Bleeding patients with consumption coagulopathy are most frequently treated with platelet transfusions and various plasma products including fresh frozen plasma and coagulation factor concentrates. Based on case reports, treatment with drotrecogin alfa (activated) or substitution of protein C have been recommended for adjuvant treatment of sepsis-related purpura fulminans.
Keywords: Sepsis; disseminated intravascular coagulation (DIC); purpura fulminans; drotrecogin alfa (activated); antithrombin